Grammatical and Lexical Features and Usage of Contractual Documents - Namsrai, Munkhtsetseg (Mongolian Journal of Applied Linguistics, 2025)
his article examines the grammatical features, lexical structure, and semantic characteristics of contract documents used in Mongolia through a corpus-linguistic approach. The study is based on a selection of 84 model contracts including lease, employment, trade, service, and cooperation agreements used by public and private sector organizations, which were analyzed using quantitative and qualitative methods with the Sketch Engine software. The compiled corpus contains 270,745 words (15,198 word forms). The findings show that the language of contracts is characterized by a standardized structure, an imperative tone, and extensive use of specialized terminology. From a lexical perspective, nouns and verbs occur with the highest frequency, and terms such as “taluud” (parties), üüreg (obligations), “erkh” (rights), and “gereenii nökhtsöl”(contractual conditions) constitute the semantic core of contractual texts. In addition, future-tense verbs with the suffix -na/-ne (e.g. “shiidervelene” (shall decide), “tölnö” (shall pay), “khariutsna” (shall be liable) occur with high frequency, expressing mandatory and obligation-imposing normative functions. Syntactically, long complex sentences with conditional clauses predominate, and the frequent use of conditional connectors such as “kherev” (if), “tokhioldold” (in the case), and “eskhül” (or) indicates an orientation toward clarity and the avoidance of ambiguity in contractual provisions. Accordingly, the study demonstrates that contract language represents a specialized, structurally stable form of language use aimed at preventing disputes and ensuring legal certainty. In terms of terminology, contractual texts predominantly employ contrastive terms denoting the legal status of the participating parties (e.g. “güitsetgegch” (contractor) – güitsetgüülegch (contracting party), “khudaldagch” (seller) –“khudaldan avagch” (buyer), “türeeslegch” (lessee) – türeeslüülegch (lessor), alongside active use of foreign terms related to economics, finance, technology, and law (such as “company”, “bank”, “arbitration”, “standard”, “license”, “technology”), reflecting the professional and international nature of contemporary contractual relations. Гэрээний бичвэр дэх хэл зүй, үгийн сангийн онцлог, хэрэглээ Хураангуй: Энэхүү өгүүлэлд Монгол Улсад хэрэглэж буй гэрээний баримт бичгийн хэл зүй, үгийн сангийн бүрдэл, утга зүйн онцлогийг хөмрөг хэл шинжлэлийн аргаар судалсан болно. Судалгаанд төрийн болон хувийн хэвшлийн байгууллагын ашигладаг түрээс, хөдөлмөр, худалдаа, үйлчилгээ, хамтын ажиллагаа зэрэг төрөл бүхий нийт 84 жишиг гэрээний эхийг сонгон авч, Sketch Engine программ ашиглан тоон болон чанарын шинжилгээ хийжээ. Бүрдүүлсэн хөмрөг нь 270 745 давтагдсан үг (давтагдаагүй тоогоор 15 198)-тэй байна. Судалгааны үр дүнгээс харахад гэрээний хэл нь стандартчилсан бүтэцтэй, захирамжлах өнгө давамгайлсан, нэр томьёо өргөн хэрэглэдэг онцлогтой байна. Үг зүйн хувьд жинхэнэ нэр, үйл үг хамгийн өндөр давтамжтай бөгөөд “талууд”, “үүрэг”, “эрх”, “гэрээний нөхцөл” зэрэг нэр томьёо гэрээний утга агуулгын цөмийг бүрдүүлж байна. Мөн ирээдүй цагийн “-на/-нэ” төгсгөлтэй үйл үгс (“шийдвэрлэнэ”, “төлнө”, “хариуцна” гэх мэт) их давтамжтай хэрэглэгдэж, заавал биелүүлэх, үүрэгжүүлэх норматив шинжийг илэрхийлдэг нь тогтоогдлоо. Өгүүлбэр зүйн хувьд нөхцөл заасан урт нийлмэл өгүүлбэр зонхилж, “хэрэв”, “тохиолдолд”, “эсхүл” зэрэг нөхцөлдүүлэн холбох үгс өргөн хэрэглэгддэг нь гэрээний заалтыг тодорхой, хоёрдмол утгагүй болгоход чиглэж байгааг харуулна. Иймээс гэрээний хэл нь маргаан үүсэхээс урьдчилан сэргийлэх, эрх зүйн баталгааг хангах зорилготой, тогтвортой бүтэц бүхий тусгай хэлний хэрэглээ болохыг уг судалгаа нотолж байна. Нэр томьёоны хувьд, гэрээний бичвэрт оролцогч талуудын эрх зүйн статустай холбоотой эсрэгцсэн нэр томьёо (жишээлбэл, “гүйцэтгэгч”–“гүйцэтгүүлэгч”, “худалдагч”–“худалдан авагч”, “түрээслэгч”–“түрээслүүлэгч”) зонхилохын зэрэгцээ эдийн засаг, санхүү, техник-технологи, хууль эрх зүйтэй холбоотой гадаад нэр томьёо (“компани”, “банк”, “арбитр”, “стандарт”, “лиценз”, “технологи” зэрэг) идэвхтэй хэрэглэгдэж, орчин үеийн гэрээний харилцааны мэргэжлийн ба олон улсын шинжийг илэрхийлж байна. Түлхүүр үг: гэрээний хэл, үгийн сан, нэр томьёо, хөмрөг хэл шинжлэл, эрх зүйн бичвэр